Aplikasi Pos Kasir Mobile Dengan Fitur Manajemen Stok Terintegrasi Untuk Mendukung Kinerja Umkm - Septiani, Minda; Candwian, Rainier (Bianglala Informatika, 2025)
Abstract - Micro, Small, and Medium Enterprises (MSMEs) are crucial to the Indonesian economy but often struggle with inefficient transaction recording and stock management. The reliance on manual processes leads to a high risk of human error, complicates inventory monitoring, and hinders swift, data-driven decision-making. This study aims to design and develop a mobile Point of Sale (POS) application using the Flutter framework, featuring integrated stock management to enhance the operational efficiency of MSMEs. The development followed a prototyping methodology, which included stages of requirement analysis, interface design, user evaluation, and final implementation. The resulting application is designed to function offline, offers an intuitive user interface, and automatically deducts raw material stock levels upon each transaction. Implementation results indicate that the application successfully minimizes recording inaccuracies, accelerates the transaction process, and significantly improves the accuracy and efficiency of inventory management. It is concluded that this application presents a viable and practical digital solution to support the day-to-day business operations and overall performance of MSMEs.Keywords: MSME, Point of Sale (POS), Inventory Management, Flutter, Mobile App.